Reversible ligation of programmed DNA-gold nanoparticle assemblies - Harimech, P; Gerrard, S; El-Sagheer, A; Brown, T; Kanaras, A (American Chemical Society, 2015)
We demonstrate a new method to reversibly cross-link DNA-nanoparticle dimers, trimers, and tetramers using light as an external stimulus. A DNA interstrand photo-cross-linking reaction is possible via ligation of a cyano-vinyl carbazole nucleoside with an opposite thymine when irradiated at 365 nm. This reaction results in nanoparticle assemblies that are not susceptible to DNA dehybridization conditions. The chemical bond between the two complementary DNA strands can be reversibly broken upon light irradiation at 312 nm. This is the first example of reversible ligation in DNA-nanoparticle assemblies using light and enables new developments in the field of programmed nanoparticle organization.